Operation strategy of energy hub for commercial buildings based on tiered temperature control. Issue 17 (24th October 2018) - Li, Yinglan
Abstract : In this study, the author considers an operation strategy of energy hubs for commercial buildings based on tiered temperature control, with the objective of balancing the operation cost and comfort level. A tiered temperature deviation penalty tariff is formulated to measure different levels of temperature deviation. Considering a set of uncertain factors, including photovoltaic output, load demand and outside temperature, this stochastic optimisation model can be converted into a mixed‐integer linear program, solved by commercial optimisation solver, CPLEX. Numerical simulations verify the efficiency of the proposed operation strategy.